Grammatical tools in terms of their classification and functions in structure (Journal of Hama University, 2025)
The great importance of tools emerged through the function they perform within structure as an important part of the parts of speech, which allowed many grammarians and scholars to consider the meanings that they convey, so they devoted many works to them, as the tool was one of the doors that brought the science of grammar into close contact with other sciences such as rhetoric, semantics and understanding jurisprudential issues as well.Their vision in studying tools was not limited to considering them within the science of grammar.In this research, we will present what grammarians say about the grammatical tool and the books written about it, explaining the functions it performs.